2022
DOI: 10.22219/mb.v12i01.15481
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Service Quality and Store Atmosphere on Customer Satisfaction at Vocational High School Business Center in Cirebon

Abstract: The purpose of this research was to find out the influence between service quality and the atmosphere of the store on customer satisfaction at the Business Center at a vocational high school in Lemahabang Cirebon. Research methods used are validity test, reliability test, and multiple Linear Regression. The analysis tool used is the SPSS tool. The results of this study explain the influence between service quality of the store and the atmosphere of the store on customer satisfaction. This indicates that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
2
1
2
Order By: Relevance
“…In providing service to customers, every party must work professionally and skillfully. The results of this research are not in line with the research conducted by Nurhajijah et al (2022) which showed a positive and significant effect of service quality on the decision to continue premium payments with customer satisfaction as a mediating variable.…”
Section: The Effect Of Service On Customer Satisfaction Through Islam...contrasting
confidence: 99%
“…In providing service to customers, every party must work professionally and skillfully. The results of this research are not in line with the research conducted by Nurhajijah et al (2022) which showed a positive and significant effect of service quality on the decision to continue premium payments with customer satisfaction as a mediating variable.…”
Section: The Effect Of Service On Customer Satisfaction Through Islam...contrasting
confidence: 99%
“…Melalui hasil pengujian yang telah dilakukan, mendapatkan hasil bahwa terdapat pengaruh signifikan dari Store Atmosphere terhadap Customer Satisfaction. Temuan tersebut berjalan satu arah dengan penelitian yang dilakukan oleh Cahaya Pratama & Kusuma Dewi, (2022); Arifin & Cahyana, (2022); dan Nurhajijah et al, (2022) yang menemukan bahwa Store Atmosphere berpengaruh secara signifikan terhadap Customer Satisfaction. Dijelaskan lebih lanjut oleh Effendy, (2019), bahwa Suasana toko, termasuk kebersihan dan elemen audio, memiliki peran krusial dalam menciptakan lingkungan yang nyaman bagi pengunjung.…”
Section: Pengaruh Store Atmosphere Terhadap Customer Satisfactionunclassified
“…Store Atmosphere, yang melibatkan aspek visual, tata letak, pencahayaan, musik, dan aroma, memainkan peran penting dalam menentukan kepuasan dan loyalitas pelanggan (Hans et al, 2023). Store Atmosphere yang nyaman dan kreatif dapat menciptakan lingkungan belanja yang menyenangkan, memengaruhi persepsi dan emosi konsumen, serta berdampak positif pada kepuasan dan niat beli ulang konsumen (Ali et al, 2022;Nurhajijah et al, 2022a;Niati, 2021). Penelitian juga menunjukkan bahwa Store Atmosphere memiliki pengaruh lebih kuat terhadap kepuasan konsumen daripada kualitas layanan (Hamdan et al, 2019), sehingga peritel perlu memastikan suasana belanja yang menarik dan menyenangkan untuk memuaskan konsumen (Soebandhi et al, 2020).…”
Section: B Kepuasan Konsumenunclassified